1956
DOI: 10.2134/agronj1956.00021962004800040011x
|View full text |Cite
|
Sign up to set email alerts
|

Cold Resistance of Parent Varieties, F2 Populations, and F3 Lines of 20 Oat Crosses1

Abstract: Synopsis Average survivals in lines of crosses among winterhardy, intermediate‐hardy, and spring oat varieties suggest that cold resistance was governed by genes having cumulative effect without important genie interactions. Some crosses showed promise as a source of combinations with more hardiness than the very winter‐hardy variety Wintok.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0

Year Published

1959
1959
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 3 publications
2
6
0
Order By: Relevance
“…Our results agreed with previous reports that controlled environment freeze tolerance in oat is a quantitative trait with moderate to high heritability (Amirshahi and Patterson, 1956; Muehlbauer et al, 1970). There was significant variation for freeze tolerance among the recombinant inbred lines (Table 1, Fig.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Our results agreed with previous reports that controlled environment freeze tolerance in oat is a quantitative trait with moderate to high heritability (Amirshahi and Patterson, 1956; Muehlbauer et al, 1970). There was significant variation for freeze tolerance among the recombinant inbred lines (Table 1, Fig.…”
Section: Resultssupporting
confidence: 93%
“…Only one other report of a bimodal distribution was found in the literature. Amirshahi and Patterson (1956) noted that a normal distribution was typical for segregating progenies in 18 of 20 populations they evaluated in greenhouse tests. One bimodal distribution and one distribution skewed toward lower survival were found in the two remaining populations.…”
Section: Field Survivalmentioning
confidence: 96%
“…The results from the F x experiment generally confirm observations elsewhere (Amirshashi & Patterson, 1956;Pfahler, 1966) that genes determining frost resistance in oats are mainly additive in their effect and do not exhibit large, non-allelic interactions. Although the marked transgression for frost resistance in some crosses in the F 2 experiment could be explained in terms of an accumulation of favourable genes, the absence of a significant Wr, Vr regression and the large SCA effects obtained suggest that non-additive gene action was more important in this subsequent experiment.…”
Section: Discussionsupporting
confidence: 87%
“…In 20 oat crosses, Amirshahi and Patterson (1956b) found that the cross with the highest heritability (95%) for freezing tolerance and the one with the most lines exceeding the freezing tolerance of Wintok was a cross between Wintok and Norline (an experimental line at the time). Unfortunately, none of those lines were entered into the UOWHN and in storage, the seed quickly lost viability.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, progress was slowed by the unpredictable occurrence of winters severe enough to kill tender genotypes and damage those of intermediate hardiness (Marshall, 1992). Early evaluations of oat in controlled environment tests designed to supplement field evaluations used juvenile whole‐plant assays (Murphy et al, 1937; Amirshahi and Patterson, 1956a, 1956b). Subsequent improvements in controlled environment techniques involved evaluation of individual lateral crown meristem tissue from which root and shoot regrowth is regenerated (Marshall, 1965).…”
mentioning
confidence: 99%